(untitled) (European Journal of Formal Sciences and Engineering, 2025)
The scope of this study was to compare various stability evaluation methods. Accordingly, most common LE approaches were compared with the advanced LE (M?P) method. Similarly, the differences in FOS computed from LE and FE analyses were compared based on a simple slope considering various load cases. In addition, two real slopes in a case study were analysed for the recorded minimum?maximum GWT, pseudo?static and dynamic conditions. Moreover, the stability evaluations of these slopes were based on both LE (M?P) and FE (PLAXIS) calculation approaches, which both utilized shear strength parameters from advanced triaxle tests. Similarly, Mohr?Coulomb model was applied in both approaches. The following conclusions are hence derived based on the reported work on both idealized and real slopes. To fulfil one of the aims of the study, the LE based methods are compared based on the factor of safety (FOS) obtained for various load combinations. The comparison is mainly based on simplified slope geometry and assumed input parameters. Among the LE methods, the Bishop simplified (BS), Janbu simplified (JS) and Janbu GPS methods are compared with the Morgenstern?Price method (M?PM). These LE methods are well established for many years, and thus some of them are still commonly used in practice for stability analysis. Moreover, the M?PM has been compared with results from the FE analyses. Compared with theFE (PLAXIS) analyses, the LE (M?PM) analyses may estimate 5 – 14percent higher FOS, depending on the conditions of a dry slope and a fully saturated slope with hydrostatic pore pressure distributions. For fully saturated conditions in the slope, inaccurate computation of stresses in LE methods may have resulted in larger difference in the computed FOS. Since, the FE software is based on stress?strain relationship, stress redistributions are surely better computed even for a complicated problem. This has been found one of the advantages in FE simulations. A parameter study shows that the application of a positive dilatancy angle in FE analysis can significantly improve the FOS (4 ? 10percent). On contrast, the shear surface optimization in LE (M?PM in SLOPE/W) analysis results in lower FOS, and thus minimizing the difference in FOS compared with FE analysis